Analisis Sektor Basis dan Shift-Share Pekerja Menurut Lapangan Usaha PDRB Propinsi Jawa Timur - Adi, Lumadya; Suprijati, Jajuk; Rosidah, Rosidah; Cahya K, Vicky (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2020)
The province that was the object of the study was East Java with the reason that it had the highest number of agricultural sector workers among the six provinces in Java island in 2011 and 2017. The first objective of this study was to know the base and non-base sectors in the GRDP by Business Field; the second objective is to examine the development of the sector regionally compared to the national and the competitiveness of the sector. The analytical tools are used: the Location Quotient analysis that is used to analyze the first goal and Shift-share analysis that is used to analyze the second goal. The results of the analysis are: The results of the LQ analysis for East Java province in 2011 and 2017 have the same base activities namely sector 1. Agriculture, Forestry, Hunting and Fisheries; and sector 2. Mining and quarrying. The results of the Shift Share analysis from 2011 to 2017 for East Java province show National Share all sectors have absorption growth rates regional labor (East Java) is higher than the national level (Java island); in the Industrial Mix column sector 1 is a sector that grows more slowly; in the Competitive Position column 3,5,6,7,8 are sectosr that has low competitiveness.